Béranger en prison : « Mes fers sont prêts ; la liberté m’inspire ; Je vais chanter son hymne glorieux » - Sophie-Anne Leterrier (Criminocorpus)
The famous Beranger was sent to prison twice during Restoration. The contribution shows how theses incarcerations contributed to its celebrity, who he was abble to present himself as a victim of oppression, through songs and illustrations. It analyses the songs writen in prison, which praise liberty and challenge the royal power.